Poetica do acaso. - Brigagao, Clovis; Quinet, Antônio (Belo Horizonte : Museu de Arte de Belo Horizonte, 1990)
Moura, Aretuza ; Moulin, Fabiola ; Nemer, José Alberto ; Penna, Júnia ; Dardot, Liliane ; Chiquitao, Luiz Antonio ; Bethônico, Mabe ; Lage, Marconi ; Negromonte, Nidya ; Homen, Ricardo ; Bethonico, Roberto ; Pessoa, Solange
Portugees
boek